Cold plasma pretreatment for transforming fruit and vegetable waste: A comprehensive review - Vaishnavi Patil; Rafeeya Shams; Kshirod Kumar Dash (Future Foods)
The application of cold plasma technology has demonstrated promise in addressing fruit and vegetable waste, providing several advantages such as waste minimization, elimination of microorganisms, and value addition. The core concept of cold plasma involves generating gas that is partially ionised and consists of charged particles, free radicals, and reactive species. The fruits and vegetable processing industry generates substantial quantity of waste through storage, processing, pulping, and juicing. The cold plasma approach disintegrates cellular structures and liberates bioactive compounds by subjecting the waste material to high-energy electrons and ions generated within the plasma. This review evaluates the application of cold plasma technology to enhance the utilisation of fruit and vegetable waste. The process of optimising parameters for cold plasma treatment, including power, voltage, treatment duration, gas selection, flow rate, exposure mode, and product composition, is illustrated. This article explores the significant effects of cold plasma on several forms of fruit and vegetable waste, such as extraction of bioactive compounds, the process of enhanced drying, inactivation of harmful microbes, and enzyme preservation. This study investigates the utilisation of cold plasma in hurdle treatments, focusing on the kinetics, modelling, and optimisation aspects of applying cold plasma to treat fruit and vegetable waste.